THE INFLUENCE OF REGIONAL ORIGINAL INCOME, GENERAL ALLOCATION FUND, SPECIAL ALLOCATION FUND ON CAPITAL EXPENDITURE OF PROVINCES IN SUMATRA AND JAVA - Ahgniya Putra; Marzuki; Wahyuddin Albra; Nurlela; Rico Nur Ilham (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This study aims to determine and analyze the effect of Regional Original Revenue, General Allocation Fund, Special Allocation Fund on Capital Expenditure of Provinces in Sumatra and Java Island. The method used to analyze the effect between the independent and dependent variables is panel data regression analysis, namely using the Eviews-10 application. The population in this study were all provinces on the islands of Sumatra and Java. The sample in this study amounted to 16 provinces, 10 provinces located on the island of Sumatra and 6 provinces located on the island of Java. The results show that local revenue has a positive and significant effect on capital expenditure in Provisions throughout Sumatra and Java. General allocation funds have no positive and insignificant effect on capital expenditures in Provisions throughout Sumatra and Java Island. Special allocation funds have no positive and insignificant effect on capital expenditures in the provinces of Sumatra and Java.